2007
DOI: 10.1001/archpedi.161.6.591
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine and Young Men Who Have Sex With Men

Abstract: A substantial percentage of YMSM in this sample used methamphetamine. Methamphetamine use is a public health problem with significant implications for the health and well-being of YMSM. Methamphetamine use was associated with human immunodeficiency virus-related risk, and patterns of use were predicted by demographic data, sexualized social contexts, and psychological variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Several studies have shown an association between drug use and sexual risk taking among MSM, particularly of the use of amphetamine type substances (Colfax et al, 2001;Garofalo, Mustanski, McKirnan, Herrick, & Donenberg, 2007). More detailed study and monitoring of the association of substance use, sexual risk taking and HIV infection in Thai MSM is therefore warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown an association between drug use and sexual risk taking among MSM, particularly of the use of amphetamine type substances (Colfax et al, 2001;Garofalo, Mustanski, McKirnan, Herrick, & Donenberg, 2007). More detailed study and monitoring of the association of substance use, sexual risk taking and HIV infection in Thai MSM is therefore warranted.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Behavior, mortality, and treatment have changed dramatically in 15 years. 7,8 A 2007 study 9 focusing on YMSM (aged 16-24 years) in Chicago, Illinois, confirmed associations found among older MSM. Although these data are informative, more geographically diverse data about methamphetamine use and HIV risk among YMSM are necessary to inform HIV prevention policies focused on this population.…”
mentioning
confidence: 83%
“…Male-male sexual risk in the prior 6-week period was evaluated at all time points using the AIDS-Risk Behavior Assessment (ARBA) adapted for young MSM (Donenberg, Emerson, Bryant, Wilson, & Weber-Shifrin, 2001; Garofalo, Herrick, Mustanski, & Donenberg, 2007; Garofalo, Mustanski, McKirnan, Herrick, & Donenberg, 2007). Variables of interest included total number of sex partners and total number of unprotected anal sex partners, and frequencies for unprotected sex acts (anal or oral), sex (oral or anal) under the influence of alcohol/drugs, and unprotected anal intercourse under the influence of alcohol/drugs.…”
Section: Methodsmentioning
confidence: 99%